L2 motivation among hearing learners of Finnish Sign Language. Issue 3 (16th March 2022) - Marton, Enikő; MacIntyre, Peter D.
ABSTRACT: The realisation of the linguistic rights of Deaf individuals is, to a considerable extent, dependent upon whether there are majority language speakers who acquire a sign language as an L2 and use their L2 skills. Still, the motivation of hearing persons in learning sign languages as L2s is a largely unmapped area. This study seeks to capture the motivation underlying the L2 use among hearing learners of Finnish Sign Language (FSL) in terms of current theorising on L2 motivation and to test the applicability of central constructs in L2 motivation research in a specific SLA context. We collected data in 2018 using an anonymous online questionnaire ( N  = 173). We tested a serial mediational model that linked L2 learning orientations and L2 learning experience, through a set of mediating variables, to L2 use. The model was statistically significant and explained 66% of the variance in L2 use. In addition, integrativeness significantly moderated the effect of L2 competence on L2 use. The findings from the quantitative analysis are enriched with the analysis of the respondents' comments. We discuss the results from the perspective of how hearing learners of sign languages can extend the communication networks of Deaf sign language users.